Keefektifan Penggunaan Model Project Based Learning dalam Pembelajaran Keterampilan Menulis Puisi Siswa - Chaerunnisa, Nurul; Adam, Andi; Rahayu, Sri (DIDAKTIS : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study aims to determine the effectiveness of using a project-based learning model on learning to write student poetry in class V SD Inpres Taeng-Taeng, Gowa Regency. This type of research is a quasi-experiment. The sample in this study was 25 students. Data collection techniques were carried out using questionnaires, writing tests, and observation sheets. The results showed that the poetry writing skills of students before the implementation of the project-based learning model were generally in the poor category and the learning outcomes on the pretest with an average value of 49.20. While the learning outcomes of students' poetry writing skills after the implementation of the project-based learning model changed to a satisfactory category and the learning outcomes of students on the posttest with an average value of 90.00 the results of descriptive analysis testing with the help of SPSS 27.0 for windows. Normality testing of pretest and post-test data has been normally distributed with sig 0.17> α = 0.05 and the results of hypothesis testing using the One sample t-test and obtained a p-value (sig. (2-tailed)) is 0.000 <0.05, so H0 is rejected and Ha is accepted, which means that the Project Based Learning model is effectively used in the poetry writing skills of fifth-grade students of SD Inpres Taeng-Taeng Gowa Regency.